Acquired von Willebrand syndrome (AVWS) type 2, characterized by decreased high molecular weight multimers, is common in children with severe pulmonary hypertension (PH) - Wieland, Ivonne; Diekmann, Franziska; Carlens, Julia; Hinze, Laura; Lambeck, Katharina; Jack, Thomas; Hansmann, Georg (Frontiers in Pediatrics, 2022)
Background and objectives Emerging evidence suggests that increased degradation of von Willebrand factor and decrease in high molecular weight multimers occurs in patients with pulmonary hypertension (PH). However, the link between acquired von Willebrand Syndrome (AVWS) type 2 and PH remains poorly understood. Material and methods We retrospectively evaluated the charts of 20 children with PH who underwent bilateral lung transplantation (LuTx) between 2013 and 2022. Von Willebrand variables were determined in 14 of these patients; 11 patients had complete diagnostics including multimer analysis. Results We confirmed AVWS in 82% of the children studied (9 of 11 patients by multimer analysis). The two remaining patients had suspected AVWS type 2 because of a VWF:Ac/VWF:Ag ratio of <0.7. Platelet dysfunction or suspicion of VWD type 1 were found in two separate patients. All but one of the 14 children with severe PH had a coagulation disorder. Most patients (9 proven, 2 suspected) had AVWS type 2. Notably, 3 of 5 patients (60%) with normal VWF:Ac/VWF:Ag ratio >0.7 had abnormal VWF multimers, indicating AVWS type 2. Hemostatic complications were observed in 4 of 12 (33%) patients with VWS and 3 of 6 (50%) patients without diagnostics and therapy. Conclusion For children with moderate to severe PH, we recommend systematic analysis of von Willebrand variables, including multimer analysis, PFA-100 and platelet function testing. Awareness of the diagnosis “AVWS” and adequate therapy may help to prevent these patients from bleeding complications in case of surgical interventions or trauma.